A case of de novo neuroendocrine prostate cancer presented with elevated level of serum CEA carrying BRCA2 mutation: case report and literature review - Han, Weizhe; Rexiati, Nihati; Yu, Fang; Wang, Yongzhi; Tian, Yueli; Wu, Jianyuan; Wang, Gang; Liu, Tao; Yang, Zhonghua (Frontiers in Oncology, 2025)
BackgroundDe novo neuroendocrine prostate cancer (NEPC) is a rare subtype of prostate cancer (PCa) and few markers are available for screening and monitoring. Potential circulating or fluid markers might facilitate early diagnosis thus improving prognosis of NEPC, especially for de novo NEPC.Case presentationA man of 71-year was presented with elevated level of serum carcinoembryonic antigen (CEA) (1296.5 ng/ml) and normal PSA (0.47ng/ml). Gastrointestinal endoscopy showed no signs of gastric or colorectal cancer. Fluorodeoxyglucose positron emission tomography-computed tomography (FDG PET-CT) and prostate-specific membrane antigen PET-CT (PSMA PET-CT) indicated prostate cancer with metastases including pelvic lymph nodes, bone as well as lung metastases. Biopsy of prostate revealed mixed carcinoma including small cell neuroendocrine carcinoma (SCNEC) and adenocarcinoma (Gleason score of 4 + 5). Immunohistochemistry (IHC) staining and next generation sequencing demonstrated a strong expression of chromogranin A (CgA), synaptophysin (SYN) and CEA, and a germline mutation in BRCA2, respectively. After a prostatic massage, an increased level of CEA (137 ng/ml vs 5 ng/ml) was detected in urine. Olaparib, a Poly ADP-ribose polymerase inhibitor (PARPi), combined with androgen deprivation therapy (ADT) were administrated. FDG PET-CT indicated tumor regression in both quantity and size three months later, and CEA levels of serum and urine decreased to 23 ng/ml and 2.4 ng/ml 4 months later, respectively.ConclusionThis is the first report of a de novo NEPC presented with an elevated level of CEA, in which CEA was also detected in urine specimen post a prostatic massage. After a combination treatment of ADT for 3 months, levels of CEA in both serum and urine decreased sharply when tumor regressed radiologically. CEA might be a marker of screening and monitoring of NEPC.